Fruit and Vegetable Consumption Associated with Reduced Risk of Epithelial Ovarian Cancer in Southern Chinese Women - Tang, Li; Lee, Andy; Su, Dada; Binns, Colin (Elsevier Inc, 2014)
Objective: To investigate the association between fruit and vegetable consumption and the risk of epithelial ovarian cancer in southern Chinese women. Methods: A case–control study was undertaken in Guangzhou, Guangdong Province, between 2006 and 2008. Participants were 500 incident ovarian cancer patients and 500 hospital-based controls. Information on habitual fruit and vegetable consumption was obtained by face-to-face interview using a validated and reliable food frequency questionnaire. Unconditional logistic regression analyses were performed to assess the association between fruit and vegetable intakes and the ovarian cancer risk. Results: The mean fruit and vegetable daily intakes of ovarian cancer patients (324.2 g (SD 161.9) and 582.7 g (SD 250.2)) were significantly lower (p < 0.001) than those of controls (477.3 g (SD 362.1) and 983.3 g (SD 739.9)). The adjusted odds ratios were 0.30 (95% confidence interval (CI) 0.21 to 0.44) and 0.07 (95% CI 0.04 to 0.12) for more than 490 g of fruits and 970 g of vegetables per day, relative to at most 320 g and 690 g per day, respectively. With the exception of lycopene, substantial risk reductions were evident for a variety of nutrients derived from fruits and vegetables. Conclusion: Consumption of fruits and vegetables was inversely associated with the incidence of epithelial ovarian cancer in southern Chinese women.